2011
DOI: 10.1097/shk.0b013e3182252ee7
|View full text |Cite
|
Sign up to set email alerts
|

The Liver as a Central Regulator of Hydrogen Sulfide

Abstract: The liver is likely exposed to high levels of H2S from endogenous hepatic synthesis and exogenous sources from the gastrointestinal tract. Little is known about the consequence of H2S exposure on the liver or hepatic regulation of H2S levels. We hypothesized that the liver has a high capacity to metabolize H2S and that H2S oxidation is decreased during sepsis; a condition in which hepatic O2 is limited and H2S synthesis is increased. Using a non-recirculating isolated and perfused liver system, we demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 41 publications
2
38
0
2
Order By: Relevance
“…Several experimental studies have demonstrated that CSE is a major participant in the maintenance of cardiovascular function (7, 14 -16). Liver is the central regulator of endogenous H 2 S production (29). Recent studies demonstrated that in liver the abundance of CSE is 60-fold higher than that of CBS, and their results showed that although CSE accounts for 97-99% of the hepatic H 2 S output, CBS accounts for only 3% of hepatic H 2 S generation capacity (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies have demonstrated that CSE is a major participant in the maintenance of cardiovascular function (7, 14 -16). Liver is the central regulator of endogenous H 2 S production (29). Recent studies demonstrated that in liver the abundance of CSE is 60-fold higher than that of CBS, and their results showed that although CSE accounts for 97-99% of the hepatic H 2 S output, CBS accounts for only 3% of hepatic H 2 S generation capacity (61).…”
Section: Discussionmentioning
confidence: 99%
“…Results from both cell culture and animal studies suggest that lower H 2 S levels may play a role in the pathogenesis of diabetic complications (5, 13, 22, 26 -28). Liver is the major tissue responsible for the production of H 2 S (29). Although Moore and co-workers (23) reported an increase in mRNA expression of both CSE and CBS in the liver tissue of * This work was supported, in whole or in part, by a National Institutes of STZ-induced T1D rats, Szabo and co-workers (22) did not find any significant changes in the protein expression of CSE or CBS in the liver tissue of STZ-diabetic rats.…”
mentioning
confidence: 99%
“…Fifth, H 2 S is rapidly removed from the circulation by tissues. Norris et al (51) have shown that the buffer-perfused rat liver removes nearly 97% H 2 S at a perfusate concentration of 150 lM H 2 S and 50% clearance at 300 lM H 2 S. Sixth, H 2 S has been shown to be rapidly consumed by tissues in the presence of oxygen (Fig. 6A) (35,56,57).…”
Section: H 2 S In Bloodmentioning
confidence: 99%
“…Biosynthesis of H 2 S has been identified in a variety of mammalian tissues. In the liver, H 2 S is endogenously produced by cystathionine b-synthase (CBS) and cystathionine c-lyase (CSE) with l-cysteine as the substrate, in addition to 3-mercaptopyruvate sulfur transferase with 3-mercaptopyruvate (33,38,50). Previous studies revealed that H 2 S plays a prominent role in inflammatory responses (22,36).…”
mentioning
confidence: 99%